A Chronic Autoimmune Dry Eye Rat Model with Increase in Effector Memory T Cells in Eyeball Tissue - Hou, Aihua (2018)
Dry eye disease is a very common condition that causes morbidity and healthcare burden and decreases the quality of life. There is a need for a suitable dry eye animal model to test novel therapeutics to treat autoimmune dry eye conditions. This protocol describes a chronic autoimmune dry eye rat model. Lewis rats were immunized with an emulsion containing lacrimal gland extract, ovalbumin, and complete Freund's adjuvant. A second immunization with the same antigens in incomplete Freund's adjuvant was administered two weeks later. These immunizations were administered subcutaneously at the base of the tail. To boost the immune response at the ocular surface and lacrimal glands, lacrimal gland extract and ovalbumin were injected into the forniceal subconjunctiva and lacrimal glands 6 weeks after the first immunization. The rats developed dry eye features, including reduced tear production, decreased tear stability, and increased corneal damage. Immune profiling by flow cytometry showed a preponderance of CD3+ effector memory T cells in the eyeball.